Optimization of Energy Distribution in Solar Panel Array Configurations by Graph Theory and Minkowski’s Paths - Merino-Córdoba, Salvador; Sanchez, Francisco; Sidrach-de-Cardona-Ortin, Mariano; Guzmán-Navarro, Francisco; Guzmán-Sepúlveda, Rafael (My University, 2016)
Nowadays, the development of the photovoltaic (PV) technology is consolidated as a source of renewable energy. The research in the topic of maximum improvement on the energy efficiency of the PV plants is today a major challenge. The main requirement for this purpose is to know the performance of each of the PV modules that integrate the PV field in real time. In this respect, a PLC communications based Smart Monitoring and Communications Module, which is able to monitor at PV level their operating parameters, has been developed at the University of Malaga. With this device you can check if any of the panels is suffering any type of overriding performance, due to a malfunction or partial shadowing of its surface. Since these fluctuations in electricity production from a single panel affect the overall sum of all panels that conform a string, it is necessary to isolate the problem and modify the routes of energy through alternative paths in case of PV panels array configuration.
Keywords: Matemáticas para ingenieros; Energy; Solar; Graph; Minkowski; Electricidad; Energía